The scribes of the Torah: the formation of the Pentateuch in its literary and historical contexts - Schmid, Konrad (Ancient Israel and its literature, 2023)
"This collection of thirty-one studies on the Pentateuch represents more than twenty years of Konrad Schmid's research and publications advocating for a new view of the Pentateuch's formation. Schmid's essays present the case for a Persian period Priestly document that provided a basic narrative thread to the Torah, which included separate, pre-Priestly components of narratives in Genesis and the Moses story. Schmid's open discussion includes evidence from various fields, such as literary history, comparative cultural history, historical linguistics, epigraphy, and archaeology. The essays are divided into eight sections usefully structured around the themes of the Pentateuch in the Enneateuch, the history of scholarship, the formation of the Torah, Genesis, the Moses story, the Priestly document, legal texts, and the Pentateuch in the history of ancient Israel's religion"-Publisher, Seite 4 of cover